Breast Imaging : a Core Review - Shah, Biren A.; Mandava, Sabala (Core review series., 2017)
The only review tool designed specifically for the Core Exam, Breast Imaging: A Core Review, 2nd Edition, covers all key aspects of breast imaging, mimicking the image-rich, multiple-choice format of the actual test. Ideal for residents getting ready for the Core Examination, as well as practitioners taking recertification exams, this unique review follows the structure and content of what you'll encounter on the test, effectively preparing you for Core Exam success!